Jenis dan Tingkat Serangan Hama Utama Tanaman Ubi Kayu (Manihot esculenta Crantz) di Kabupaten Lima Puluh Kota: english - Hidrayani, Hidrayani; Khairul, Ujang; Ratib, Fadilla; Ikhsan, Zahlul (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2019)
Pests are one of constrains in cassava production. The research was done in cassava plantation in Lima Puluh Kota with the objectives were to determine the species of major pests of cassava and their damages. A survey was conducted in five subdistricts, Akabiluru, Guguak, Harau, Lareh Sago Halaban and Situjuah Limo Nagari. Twenty sampled plants were taken in 400 m2 plot laying in the middle of 0,5 hectar cassava plantation, 4-5 months. Four species of pests were found to attack cassava plants in Lima Puluh i.e: Paracoccus marginatus, Pseudococcus jackbeardsleyi, and Ferrisia virgata, whitefly, Aleurodicus dispersus. The three mealybugs caused percentage of plant attacked 85.5 %, percentage of leaf plant attacked 8.61 %, pest population 52.29 individual per plant with damage intensity was high. Whitefly caused percentage of plant attacked 12%, percentage of leaf plants attacked 0.77%, pest population 1.51 individual per plant.